Auditoría operativa y su incidencia en la eficacia de los procesos de madera verde de la empresa plantaciones de balsa Plantabal S.A. cantón Quevedo. año 2014 - Briones Mindiola, Carmen Juliana (2015)
The research was conducted at the company Plantabal SA, the canton Quevedo, Los Rios province, 4.5 kilometer road to Valencia. Whose geographical location is 1 ° 20 '30 "south latitude and 79 ° 28' 30" west longitude, to a height of 73 meters, the general objective is sought to establish an operational audit and its impact on the processes of green wood Company Balsa Plantations Plantabal SA; The specific objectives were: to diagnose the functional structure, applying the tools of internal control assessment, determine the efficiency and effectiveness of processes and issue the report with their comments; deductive and analytical in order to define the problem research proposal - the inductive methods used. The investigative phase, of information gathering lasted 120 days. The results show that the functional structure of the area of green wood Balsa Plantations Plantabal SA Company, contains specific programs or procedures for management indicators that have been set for each of the areas of the company are properly implemented and evaluated in order to objectively analyze the situation of these and how they affect the economic performance of the company In addition to applying the tools of internal control assessment in the area of green wood plantations Balsa Plantabal SA Company, assessing the internal control system, as it allowed us to determine shortcomings and identify opportunities for improvements, very necessary aspects in the marketing process With the report with their comments, conclusions and recommendations to the Board of the company maximum it was exposed to improve the processes described.